2016
DOI: 10.5455/ijmsph.2016.060420153
|View full text |Cite
|
Sign up to set email alerts
|

Profile of autopsy cases at New Civil Hospital, Surat: a retrospective study

Abstract: in our day-today life. While some are able to take up the pressures of life, others are not able to face it; hence, they end up their lives, making lives miserable for the family members. This study aims to set up a profile of deaths owing to natural or unnatural causes, so that we can direct rigorous efforts to curb their incidence. India is a developing country with increasing industrialization and urbanization. Surat is regarded as having a large industrial zone. The Surat city is a major silk and cotton te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
5
2
1
Order By: Relevance
“…Rural residents were 67.9% and only 32.1% were from Urban. This finding is contradicting to results of other studies done by Radhakrishna KV [13] et al and Patel JB [14] et al in which Urban residents were in majority.This difference is due to our centre serves more rural population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Rural residents were 67.9% and only 32.1% were from Urban. This finding is contradicting to results of other studies done by Radhakrishna KV [13] et al and Patel JB [14] et al in which Urban residents were in majority.This difference is due to our centre serves more rural population.…”
Section: Discussioncontrasting
confidence: 99%
“…According to month wise distribution of cases, findings of our study showed more number of cases between April to June. Similar findings are seen in studies by Patel et al [14] and Awdesh et al [15] .…”
Section: Discussionsupporting
confidence: 92%
“…According to month wise distribution of cases, findings of our study showed more number of cases between April to July (45.75%). Similar findings are seen in studies by Patel et al 11 and Awdesh et al 9…”
Section: Discussionsupporting
confidence: 91%
“…The preferred method of committing suicide in China was by hanging whilst that of India was mostly via thermal burns. [6,13] The forensic autopsy and the police reports showed road traffic accident as the ultimate manner of death of all medicolegal autopsies in present study. This was followed cardiovascular and respiratory diseases.…”
Section: Discussionsupporting
confidence: 52%